Understanding and Navigating Challenging Behaviors in Early Childhood Education - Vưu Anh Tài (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
In the field of early childhood education, the purpose of this research was to better comprehend and manage problematic behaviors. The quantitative method was utilized in order to acquire data from the fifty instructors who were working in early childhood education environments. The prevalence of problematic behaviors, instructors' confidence in confronting them, and the use of evidence-based interventions to support children's social-emotional development were all analyzed using descriptive statistics. According to the findings, difficult behaviors are relatively prevalent in early childhood education; however, educators typically feel confident in their ability to address them and are using evidence-based interventions to support the development of children. On the other hand, the research underscored the necessity of continuing training and assistance in order to encourage favorable outcomes for all children who participate in early childhood education. The findings add to our knowledge of how teachers handle problematic behaviors in the classroom and have significant repercussions for both future research and practice in the field of early childhood education.